An overview of systematic evidence on oral microbial composition for orodigestive tract cancer risk - Steena Kuriakose; R S Vinutha; Krithiga Shridhar (Annals of Oncology Research and Therapy, 2022)
We summarized published systematic reviews of studies evaluating oral microbial composition for orodigestive cancer risk. A PubMed literature search was conducted for the most recent time period between January 1, 2019 and April 25, 2022, for systematic reviews in English language using keywords and MeSH terms in combination. Seven systematic reviews included all published observational studies until June 2021 with 8–34 individual studies evaluated in each of those reviews. The individual studies were primarily hospital-based case–control studies with only six population-based evaluations (five prospective; one case control). The oral cavity, oro-and hypopharynx, esophagus, stomach, colorectum, liver, and pancreas were the cancer sites investigated. Saliva, oral rinse, subgingival and dental plaque, surface tissue swabs, biopsy tissue specimens, and tongue-coating samples were analyzed for oral microbial composition using next-generation sequencing techniques primarily 16S rRNA sequencing. The total sample size in different reviews ranged between 578 and 2769 cases and 261 and 3519 controls with small individual studies (3–250 cases and 2–465 controls). To date, there were four hospital-based case–control studies from India. The overall findings were restricted to bacterial communities. Compared to controls, the alpha-and beta-diversity for these cancer sites either showed no difference or inconsistent patterns. A few noteworthy differential abundances at the genus level for selected cancer sites included oral cavity – increased Fusobacterium, Parvimonas, and Peptostreptococcus and decreased Streptococcus, colorectum – increased Fusobacterium, Gemella, Peptostreptococcus, Prevotella, and Lautropia, pancreas – increased Porphyromonas and Alloprevotella, and esophagus – increased Tannerella. For clinical and public health translation, the identified leads might require validations in prospective population-based studies with rigorous methods, species-level characterizations, and functional analysis to prove causal associations.